EFEKTIVITAS PROJECT BASED LEARNING (PjBL) DALAM PEMBELAJARAN BAHASA ARAB DI MTs NIPI RAKHA AMUNTAI - Iqbal, Muhammad; Selvia (Al-Ma'had: Jurnal Ilmiah Kepesantrenan, 2024)
In learning at school, there are still female students who do not master Arabic vocabulary, due to less varied learning methods and differences in school backgrounds, some of them have never studied Arabic. In response to this, a more interesting and varied learning method is needed in accordance with the applicable curriculum so that students do not feel bored and get equal opportunities to gain knowledge through meaningful learning. This research aims to find out whether or not the Arabic language skills of female students at MTs NIPI RAKHA Amuntai are effective before and after using PjBL. This research uses a quantitative research method of the Pre-Experimental Design type with the form of One Group Pretest Posttest design. The results of this research show: The Arabic language skills of female students at MTs NIPI RAKHA Amuntai before using PjBL with pretest calculations had an average of 64.19, which means that the students' pretest scores tend to be low (incomplete), however after using PjBL with posttest calculations it has an average of 82.58, which means that the students' posttest scores are categorized as high (completed) or have increased. Based on the results of the analysis using the Paired Sample T Test, the research results showed that PjBL learning was proven to be effectively used to improve female students' abilities regarding vocabulary mastery in Arabic language learning at MTs NIPI RAKHA Amuntai which was marked with a Sig value. (2-tailed) is 0.000 and the significance value is <0.05, then Ho is rejected and Ha is accepted. With an average difference between the pretest and posttest of 18,387.